Rare malignant indications for liver transplantation: a collaborative transplant study report - Houben, Philipp; Schimmack, Simon; Unterrainer, Christian; Döhler, Bernd; Mehrabi, Arianeb; Süsal, Caner (Frontiers in Surgery, 2021)
Introduction: Hepatocellular carcinoma (HCC) is by far the leading malignant indication for liver transplantation (LT). Few other malignancies, including cholangiocellular carcinoma (CCC), metastases from neuroendocrine tumors (NET), and sarcomas of the liver (LSAR), also are commonly accepted indications for LT. However, there is limited information on their outcome after LT.Methods: Graft and patient survival in 14,623 LTs performed in patients with hepatocellular carcinoma, CCC, NET, and LSAR from 1988 to 2017 and reported to the Collaborative Transplant Study were analyzed.Results: The study group consisted of 13,862 patients who had HCC (94.8%), 498 (3.4%) who had CCC, 100 (0.7%) who had NET, and 163 (1.1%) who had LSAR. CCC patients showed a 5-year graft survival rate of 32.1%, strikingly lower than the 63.2% rate in HCC, 51.6% rate in NET, and 64.5% rate in LSAR patients (P < 0.001 for all vs. CCC). Multivariable Cox regression analysis revealed a significantly higher risk of graft loss and death due to cancer during the first five post-transplant years in CCC vs. HCC patients (HR 1.77 and 2.56; P < 0.001 for both). The same risks were increased also in NET and LSAR patients but did not reach statistical significance.Conclusion: Among patients with rare malignant indications for LT, CCC patients showed significantly impaired graft as well as patient survival compared to HCC patients. The observed differences might challenge traditional decision-making processes for LT indication and palliative treatment in specific hepatic malignancies.
Gesehen am 20.01.2022